2019
DOI: 10.5614/j.eng.technol.sci.2019.51.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of One-Dimensional Seismic Site Response Analyses Based on Local Soil Condition of Jakarta

Abstract: Seismic site response analysis is used to estimate the response of soil deposits during seismic loading at any depth of interest and to interpret time histories as well as response spectra. This type of analysis involves many parameters that can affect the character of ground shaking. It is important to know the effect of these parameters in order to perform reliable seismic hazard evaluation at a site. This paper presents the effects of several parameters toward the characteristics of surface response spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The results were in alignment to the amplification factor available in Indonesian seismic code (Indonesian Standard Code, 2012). Different from Delfebriyadi et al (2019), non-linear site response study conducted by Misliniyati et al, (2019) using DEEPSOIL software shows different trend. They performed parametric studies by varying the soil constitutive models, layer thickness, depth of bedrock, shear wave velocity of bedrock, and soil dynamic properties curve models.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results were in alignment to the amplification factor available in Indonesian seismic code (Indonesian Standard Code, 2012). Different from Delfebriyadi et al (2019), non-linear site response study conducted by Misliniyati et al, (2019) using DEEPSOIL software shows different trend. They performed parametric studies by varying the soil constitutive models, layer thickness, depth of bedrock, shear wave velocity of bedrock, and soil dynamic properties curve models.…”
Section: Introductionmentioning
confidence: 89%
“…Referring to SNI 1726(Indonesian Standard Code, 2019, site amplification factor is divided into several groups based on soil classification in which the values for period spectra tend to increase as the soil becomes softer. Previous study of site response in Jakarta, Indonesia has been conducted by several researchers (Delfebriyadi et al, (2019), Misliniyati et al, (2019), and Sengara & Komerdevi, (2020)) using 1D site response analysis with NERA, DEEPSOIL, and also STRATA (Kottke & Rathje, 2009). There was a previous study on site response of Surabaya by Irsyam et al, (2009), but the 2002 Seismic design code which had lower level of earthquakes was used.…”
Section: Introductionmentioning
confidence: 99%
“…A complete and thorough explanation of the procedures for generating seismic ground motion at ground surface and the methodology to do a site response analysis have been presented by Hutapea, et al [4] and Irsyam, et al [5]. Based on the local soil conditions of Jakarta, the parametric study on site response analysis conducted by Misliniyati, et al [6] evaluated the effect of several input parameters (i.e. the Vs at bedrock, the plasticity index of the local site, the amplitude and frequency content of the input motion) on the characteristics of ground surface motion.…”
Section: Methodsmentioning
confidence: 99%
“…The model overestimated the shear stress that occurs once the shear strain is perfectly plastic [13]. The shear strength of the weakest layer controls the maximum acceleration, which indicates an overestimation of the peak ground acceleration above the layer [41,42]. In conclusion, the seismic ground response analysis showed that the extended hyperbolic model proposed by Hashash, et al [5] is the most appropriate model.…”
Section: Time History and Frequency Contentmentioning
confidence: 99%